Hunting for differentially expressed genes - Vedoy,C.G. (1999)
Differentially expressed genes are usually identified by comparing steady-state mRNA concentrations. Several methods have been used for this purpose, including differential hybridization, cDNA subtraction, differential display and, more recently, DNA chips. Subtractive hybridization has significantly improved after the polymerase chain reaction was incorporated into the original method and many new protocols have been established. Recently, the availability of the well-known coding sequences for some organisms has greatly facilitated gene expression analysis using high-density microarrays. Here, we describe some of these modifications and discuss the benefits and drawbacks of the various methods corresponding to the main advances in this field.